STUDY OF THE IMPACT OF INTERNATIONAL FINANCIAL CRISIS ON TAIWAN’S GAME INDUSTRY AND INVESTORS - Tsai, Bi-Huei (International Journal of Management, Innovation & Entrepreneurial Research, 2018)
Purpose of study: This study investigates the change of stock returns during the Lehman Brother’s announcement of bankruptcy in 2008 for the Taiwanese listed video game companies. We further explore the change of stock returns for the Taiwanese listed video game companies after Taiwan’s economy recovers from Lehman Brother’s bankruptcy. Methodology: This study utilizes the event study method to statistically test abnormal returns so as to understand whether the Lehman Brother’s bankruptcy-related event affects stock prices and whether securities prices reflect Lehman Brother’s bankruptcy-related information. Main Findings: The results show a significant negative abnormal rate during Lehman Brother’s declaration of bankruptcy on Sep. 15, 2008. Investors were affected by the financial crisis caused by Lehman Brother’s bankruptcy and fully reflected on the stock prices of that day. In addition, our results show that video game companies have significantly positive returns when most Taiwanese electronics firms stop no-pay leave on March 31, 2009. It represents investors were encouraged by this information and fully reflected on the stock prices. Implications: The results support the efficient market hypothesis. The pattern of CARs experiences a constant increase and displays the apparent price rise during the announcement of no-pay leave stop. The positive abnormal returns are accompanied by the economic recovery. Originality/Novelty: This investigation for the first time chooses the stop of no-pay leave as the indicator of economic recovery from financial crisis. Our analysis novel explores the impact of the financial crisis and the economic recovery on the game industry simultaneously and the results show significantly different market reactions between the occurrence of the financial crisis and economic recovery.